The initial accountant competency of final year accounting students - Weli Weli; Almatius Setya Marsudi (Institute of Advanced Engineering and Science, 2022)
The development of information technology towards the 4th industrial revolution era brought changes to business processes in various industries, which will eventually have an impact on jobs in the accounting field. Accountants must be adaptable and competent to work as accounting professionals. Therefore, this study aimed to analyze the perceptions of final-year accounting students regarding knowledge competence, soft skills, information technology capabilities, and perceptions of readiness to enter the workforce. It also analyzed whether these competencies affect students' readiness to enter the workforce. In this study, the soft skills competencies are dimensions of intellectual, personal, organizational, internal, and communication competencies, and ethics in accounting. The data was collected using a questionnaire based Google Form given to several universities in Indonesia that were willing to distribute the forms to their accounting students. A descriptive method was used for data and confirmatory factor analysis and data processing was performed with the help of statistical package for the social sciences (SPSS) and partial least squares (SmartPLS) programs. The results showed that soft skills competencies had a higher score compared to accounting and information technology competencies. Furthermore, there was a significant influence between competence and work readiness of accounting students. This study provides information in the preparation of the accounting curriculum to consider various competencies following industry needs.